2016
DOI: 10.3389/fnut.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Two Serotype 1/2b Listeria monocytogenes Isolates from Analogous Environmental Niches Demonstrates the Influence of Hypervariable Hotspots in Defining Pathogenesis

Abstract: The vast majority of clinical human listeriosis cases are caused by serotype 1/2a, 1/2b, 1/2c, and 4b isolates of Listeria monocytogenes. The ability of L. monocytogenes to establish a systemic listeriosis infection within a host organism relies on a combination of genes that are involved in cell recognition, internalization, evasion of host defenses, and in vitro survival and growth. Recently, whole genome sequencing and comparative genomic analysis have proven to be powerful tools for the identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…This finding supports previous studies that identified the presence of internalin genes in L. monocytogenes isolates from irrigation water and agricultural soil in South Africa's Eastern Cape Province (Iwu et al, 2022). Moreover, the inlA gene has long been known to be conserved in L. monocytogenes (Poyart et al, 1996), and has been implicated in the establishment of listeriosis (Chatterjee, 2006;Ingeborg, 2011;Casey et al, 2016). The surface internalin A (inlA) protein, a product of the inlA gene, plays an important role in the invasion of L. monocytogenes into mammalian cells (Werbrouck et al, 2006;Phelps et al, 2018).…”
Section: Resultssupporting
confidence: 89%
“…This finding supports previous studies that identified the presence of internalin genes in L. monocytogenes isolates from irrigation water and agricultural soil in South Africa's Eastern Cape Province (Iwu et al, 2022). Moreover, the inlA gene has long been known to be conserved in L. monocytogenes (Poyart et al, 1996), and has been implicated in the establishment of listeriosis (Chatterjee, 2006;Ingeborg, 2011;Casey et al, 2016). The surface internalin A (inlA) protein, a product of the inlA gene, plays an important role in the invasion of L. monocytogenes into mammalian cells (Werbrouck et al, 2006;Phelps et al, 2018).…”
Section: Resultssupporting
confidence: 89%
“…Listeriosis outbreak involving serotype 1/2b from cheese has also been reported [ 53 ]. Also, serotype 1/2b has been found in cases of bovine mastitis [ 54 ]. The presence of these serotypes in dairy samples suggest that they could constitute a potential health threat to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic analyses of L. monocytogenes strain EGD-e with nonpathogenic L. innocua strain CLIP1182 revealed potential genetic differences responsible for pathogenicity [23]. Since then, several virulence factors were identified in L. monocytogenes by comparative genomics [12,24]. In the current study, we assessed the contribution to virulence of five L. monocytogenes genes identified solely by comparative genomics.…”
Section: Introductionmentioning
confidence: 99%